F(x)= 2x-6
Y=Mx+b
B= y intercept= -6
M= how many times it went up so 2 times
Hope this helped :))
Try this option:
the rule: if f(-x)=f(x), then the function f(x) is even, if f(-x)=-f(x) then the function is odd.
1. f(x)=-5x⁴-2;
if to substitute x→(-x), then f(-x)=-5*(-x)⁴-2; ⇔ f(-x)=-5x⁴-2, in other words f(x)=f(-x), it means that this function is even.
2. f(x)=x³+2x.
if to substitute x→(-x), then f(-x)=(-x)³+2*(-x); ⇔ f(-x)=-(x³+2x), in other words f(-x)=-f(x), it means that this function is odd.
Answer:
Becky, because her justification for the second statement should be "definition of supplementary angles" rather than "angle addition postulate."
Step-by-step explanation:
Becky completed the proof incorrectly because her justification for the second statement is not totally correct.
Angle addition postulate does not really apply here, as the sum of 2 angles may not give you exactly 180°.
However, the second statement, m<AKG + m<GKB = 180° and m<GKB + m<HKB = 180°, can be justified by the "Definition of Supplementary Angles".
The sum of supplementary angles = 180°.
Therefore, Becky completed the proof incorrectly.
Given:
AD is diameter of the circle, AB is the tangent, and measure of arc ADC is 228 degrees.
To find:
The
and
.
Solution:
AD is diameter of the circle. So, the measure of arc AD is 180 degrees.
![m(arcADC)=m(arcAD)+m(arcDC)](https://tex.z-dn.net/?f=m%28arcADC%29%3Dm%28arcAD%29%2Bm%28arcDC%29)
![228^\circ=180^\circ+m(arcDC)](https://tex.z-dn.net/?f=228%5E%5Ccirc%3D180%5E%5Ccirc%2Bm%28arcDC%29)
![228^\circ-180^\circ+=m(arcDC)](https://tex.z-dn.net/?f=228%5E%5Ccirc-180%5E%5Ccirc%2B%3Dm%28arcDC%29)
![48^\circ+=m(arcDC)](https://tex.z-dn.net/?f=48%5E%5Ccirc%2B%3Dm%28arcDC%29)
The measure inscribed angle is half of the corresponding subtended arc.
![m\angle CAD=\dfrac{1}{2}\times m(arcDC)](https://tex.z-dn.net/?f=m%5Cangle%20CAD%3D%5Cdfrac%7B1%7D%7B2%7D%5Ctimes%20m%28arcDC%29)
![m\angle CAD=\dfrac{1}{2}\times 48^\circ](https://tex.z-dn.net/?f=m%5Cangle%20CAD%3D%5Cdfrac%7B1%7D%7B2%7D%5Ctimes%2048%5E%5Ccirc)
![m\angle CAD=24^\circ](https://tex.z-dn.net/?f=m%5Cangle%20CAD%3D24%5E%5Ccirc)
AB is the tangent. So,
because radius is perpendicular on the tangent and the point of tangency.
![m\angle BAD=m\angle CAB+m\angle CAD](https://tex.z-dn.net/?f=m%5Cangle%20BAD%3Dm%5Cangle%20CAB%2Bm%5Cangle%20CAD)
![90^\circ=m\angle CAB+24^\circ](https://tex.z-dn.net/?f=90%5E%5Ccirc%3Dm%5Cangle%20CAB%2B24%5E%5Ccirc)
![90^\circ -24^\circ=m\angle CAB](https://tex.z-dn.net/?f=90%5E%5Ccirc%20-24%5E%5Ccirc%3Dm%5Cangle%20CAB)
![66^\circ=m\angle CAB](https://tex.z-dn.net/?f=66%5E%5Ccirc%3Dm%5Cangle%20CAB)
Therefore,
and
.
Answer:
3.1415926535 8979
Step-by-step explanation:
bruh just search it in google